Comparison between refractive outcomes of femtosecond laser-assisted cataract surgery and standard phacoemulsification - Shaheen, Mohamed Shafik (BMC Ophthalmol, 2020)
BACKGROUND: To compare the visual and refractive outcomes of femtosecond laser assisted cataract surgery (FLACS) using Victus platform (Technolas Bausch and Lomb (B&L), Munich, Germany) and conventional phacoemulsification cataract surgery (CPCS). METHODS: A retrospective study of 100 eyes operated for cataract. FLACS was performed in 50 eyes and CPCS was done in another 50 eyes. Preoperative and 6 months postoperative visual and refractive evaluation (efficacy, safety, predictability, and surgically induced astigmatism) as well as higher-order aberrations were analyzed. Efficacy index which equals post-operative mean of uncorrected distance visual acuity (UDVA) divided by preoperative mean corrected distance visual acuity (CDVA) was calculated in both groups. Safety index equals post-operative mean of corrected distance visual acuity (CDVA) divided by preoperative mean CDVA. RESULTS: Logarithm of the Minimum Angle of Resolution (LogMAR), UDVA improved in both groups after surgery (p < 0.05). It was 0.23 ± 0.20 and 0.291 ± 0.311 log MAR in FLACS and CPCS groups respectively. Safety index was 1.777 in FLACS group and 1.744 in CPCS groups showing high degree of safety of both measures. Mean surgically induced astigmatism (SIA) was 0.35 ± 0.67 D and 0.901 ± 0.882 D in FLACS and CPCS groups respectively (p = 0.015). The post-operative comparison between both groups was in favor of CPCS group vs. FLACS group regarding total aberrations (0.563 ± 0.386 vs. 0.91 ± 1.20) (p = 0.03), while low order aberrations were significantly less in FLACS group vs. CPCS group (0.64 + 0.63 vs. 2.07 + 3.15) (p = 0.027). RMS high order aberration was higher in FLACS group vs. CPCS group but of no statistical significance 0.54 ± 0.96 vs. 0.328 ± 0.360 (p = 0.082). CONCLUSION: Femtosecond laser -assisted cataract surgery was a safe and precise procedure but enhanced visual outcomes only minimally when compared to conventional cataract surgery in experienced hands. Both FLACS and manual surgeries can achieve a high efficacy, predictability and safety with slight superior outcomes in FLACS. TRIAL REGISTRATION NUMBER: PACTR201804003256258 (date: 27 Mar 2018) Available at: https://pactr.samrc.ac.za/